IMPLIKASI KEPRIBADIAN GEN Z BAGI DAYA SAING ORGANISASI: SUATU KAJIAN SYTEMATIC LITERATURE REVIEW - Ismail Rasulong; Rudi Salam; Muhammad Yusuf; Irwan Abdullah (Prodi Manajemen Universitas Syekh Yusuf Al Makassari Gowa, 2024)
Generation Z, or Gen Z, provides a fresh and unique viewpoint on the administration of organizations. The Z-generation cohort has assimilated into the workforce and amalgamated with the elder generation. Their proficiency in digital technologies and propensity for autonomy pose both advantages and challenges to the competitiveness of organizations. This study conducts a comprehensive analysis of literature by closely examining fifty scholarly publications that have been published in the past eight years. The findings emphasize the importance of understanding the preferences and characteristics that Generation Z considers when choosing a workplace. Generation Z expects a management style that promotes teamwork and openness, combined with competitive pay, flexible work arrangements, and a strong company culture. They embody innovation, dynamism, and technological proficiency, making them a valuable resource for instigating transformations and augmenting competitiveness within organizations. Moreover, it is imperative for companies to grasp the behaviors, values, and operational methodologies of Gen Z. Consequently, organizations must dedicate resources to constructing a work environment that is both forward-thinking and diverse.